YOUTH PARTICIPATION IN GLOBAL GOVERNANCE: OPPORTUNITIES AND CHALLENGES: OPPORTUNITIES AND CHALLENGES - Marah, Thomas Sheku; Pradhan, Happy David; SHUHOOD, FATHIMA ADILA (Journal of Governance and Public Administration, 2024)
The inclusion of youth in government decision-making processes is an increasingly prevalent trend within the context of global governance. The world’s population has more than 1.8 billion youths aged between 15 and 30 and therefore their integration into policy frameworks and decision-making processes is essential for achieving sustainable development goal, peace creation, and advancement of technologies. The youth are the key agent of change who are proficient in technology, optimistic about the future, and determined as they always seek to change. Unfortunately, they are on the other hand subjected to and required to endure in the face of tokenistic representation, disillusionment and institutions resistant to change. This paper seeks to evaluate the global governance youth participation by looking at the existing frameworks, examples of best practices, and the most systemic challenges that are preventing full integration of youth in global governance. Specifically, the findings show how emerging youth policies such as the African Union Youth Charter and the Commonwealth Youth Council, as well as youth-led social movements (e.g., Fridays for Future), are already influencing international policies. It also highlights the importance of significant institutional reforms as well as the infusion of consistent and sustainable investment to enhance the youth participation in global governance. This paper starts with practical policy recommendations such as capacity building and strengthening measures and recruitment case studies of inclusion of youth in governance. All in all, youth should be prepared with an active role in making the decisions that shape their future through strengthening measures through financial independence and meaningful educational reforms.